The food52 cookbook ebook 140 winning recipes from exceptional home cooks. - Hesser, Amanda (2024)
" A testament to crowd-sourcing, to accomplished cooks who don't necessarily blog, and to Food52.com's smart curating." — Washington Post The Best Cooks Are Home Cooks Accomplished food writers and editors Amanda Hesser and Merrill Stubbs had a mission: to discover and celebrate the best home cooks in the country. Each week for fifty-two weeks, they ran recipe contests on their website, Food52.com, and the 140 winning recipes make up this book. They include: Double Chocolate Espresso Cookies Secret Ingredient Beef Stew Simple Summer Peach Cake Wishbone Roast Chicken with Herb Butter These recipes prove the truth that great home cooking doesn't have to be complicated or precious to be memorable. This book captures the community spirit that has made Food52 a success. It features Amanda's and Merrill's thoughts and tips on every recipe, plus behind-the-scenes photos, reader comments, and portraits of the contributors—putting you right in the kitchen with America's most talented cooks. "There's something for everyone . . . from crowd-pleasing Zucchini Pancakes to elegant Risotto Rosso. And isn't it heartwarming that something as ephemeral as a blog, about something as transient as food, might be just good enough to make it to your permanent bookshelf? Take a bow, home cooks." —NPR "Even readers with a shelf full of cookbooks will appreciate the book's broad, creative collection. . . . Cooks of all skill levels will find plenty of room to stretch." — Publishers Weekly, starred review